2015
DOI: 10.1111/eve.12384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a pelleted supplement fed during and after omeprazole treatment on nonglandular gastric ulcer scores and gastric juice pH in horses

Abstract: Summary Gastric ulcers are common in horses. The purpose of this study was to test the effect of a commercially available supplement, SmartGut® Ultra pellets (SmGU) on gastric ulcer scores and gastric juice pH after omeprazole treatment in stall‐confined horses. Eight Thoroughbred horses were studied in a 2‐period, 2‐treatment crossover design, where the SmGU (40 g, twice daily) was mixed in grain feed. Horses were stall‐confined and treated with the supplement or control for 6 weeks, consisting of 2 weeks (Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In these studies, gastric juice was aspirated through the endoscope biopsy channel just prior to insufflation. In these studies gastric juice pH was significantly higher (pH >4.0) 17-19 h after the 14th daily dose of omeprazole (Andrews et al 2006b(Andrews et al , 2015Videla et al 2011;Huff et al 2012;Loftin et al 2012;Woodward et al 2014). The collection of gastric juice during the gastroscopic examination is relatively simple, but daily fluctuations in pH, pH profile or pH status in the fed state cannot be evaluated.…”
mentioning
confidence: 99%
“…In these studies, gastric juice was aspirated through the endoscope biopsy channel just prior to insufflation. In these studies gastric juice pH was significantly higher (pH >4.0) 17-19 h after the 14th daily dose of omeprazole (Andrews et al 2006b(Andrews et al , 2015Videla et al 2011;Huff et al 2012;Loftin et al 2012;Woodward et al 2014). The collection of gastric juice during the gastroscopic examination is relatively simple, but daily fluctuations in pH, pH profile or pH status in the fed state cannot be evaluated.…”
mentioning
confidence: 99%
“…12 h, decreased the number of squamous ulcers 14 days after omeprazole treatment was discontinued and during a week of intermittent feed‐deprivation (Andrews et al . ). Such supplements might be an alternative to long‐term use of pharmaceutical agents to protect the squamous mucosa from acid injury.…”
Section: Dietary Supplementsmentioning
confidence: 97%
“…Sykes et al (2013) [21] reported that a combination of pectin-lecithin complex (Apolectol®), live yeast and magnesium hydroxide, when supplemented for [24][25][26][27] days reduced the severity of glandular and squamous gastric ulcers in Thoroughbred horses in race training. Andrews [22] reported that a supplement containing a number of ingredients, including pectin, lecithin, sea buckthorn and L-Glutamine may The aim of the current study was to examine the hypothesis that Succeed® is not inferior to omeprazole for the treatment of squamous ulceration in horses in race training over the course of 90 days. at the time of initiation of the trial.…”
Section: Introductionmentioning
confidence: 99%